The value of network neutrality to European consumers - René Arnold; Martin Waldburger; Bastian Morasch; Frieder Schmid; Anna Schneider (International Telecommunications Society (ITS), 2015)
In light of the lack of studies into the value of network neutrality to consumers, BEREC has commissioned a European (CR; CZ; EL; SE) mixed-methods study to explore this issue. This paper presents selected results of this study. To understand the value of network neutrality to European consumers, one first has to explore the role that the Internet plays in consumers' lives. We find that whilst the Internet has become very important to the majority of consumers across the four test areas studied in this paper, its role in consumers' lives differs greatly depending on the national culture, but also to some extent on the quality of Internet access available in the specific country. Consumers usually find being able to access all content and applications on the Internet fundamental to their quality of experience. They do not want to see their access restricted in any way, but many find it fair if emergency relief services or the police receive prioritised access. The same is true if others pay extra for prioritised access to specific applications as long as this does not compromise the experience of those who do not pay extra. Taking a closer look at consumers' understanding and conceptualisation of network neutrality supports that consumers do not have a clear understanding of the concept. However, they care strongly about the effects deviations from network neutrality have for their own quality of experience or the quality of experience of others. The conjoint analysis conducted for this study highlights the importance of network neutrality-related product attributes for consumers' purchase decisions. In fact, they make up around half of their purchase decisions for at home Internet access. A closer analysis of the part-worth utilities reveals a surprising preference for the best effort Internet access to applications over the prioritised one. It seems likely that this result is due to their lack of experience with prioritised services. The paper discusses various alternative explanations of this preference pattern. In line with expectations, the conjoint analysis also finds that any restrictions of consumers' access results in a significantly reduced willingness-to-pay for their at home Internet access.
Keywords: 330